Analisis Kualitas Pelayanan Dengan Metode Importance-Performance Analysis dan Metode Kano Pada PT XYZ - Lesmono Nicko Louis Renando; Anggoro Prasetyo Utomo; Ricky Doddy Sianturi (Universitas Binaniaga Indonesia, 2023)
PT XYZ is the exclusive provider of rail transportation services for goods delivery in Indonesia. Interviews were conducted with customers related to PT XYZ's services. Based on the results of the interviews, it can be seen that the current service is not satisfying to customers, so it is necessary to conduct research on the quality of services currently provided by PT XYZ. The purpose of this study is to analyze PT XYZ's service quality, analyze which attributes need to be improved and maintained, and set priorities for attributes that need to be improved. The method to be used is IPA and Kano using SERVQUAL. The IPA method is used to map the gap between performance and customer expectations in a Cartesian diagram. Furthermore, calculations are carried out using the Kano method, so that the priority of service attributes that will be improved is produced. There are 15 service attributes to be analyzed in this research. After processing data on 50 respondents, the results of this study indicate that PT XYZ's service quality from the customer's point of view is not satisfactory. Therefore, it is necessary to improve service quality at PT XYZ. There are 3 attributes that are prioritized for improvement and 6 attributes that need to be maintained. Business Process Model and Notation (BPMN) will help PT XYZ improve service quality by utilizing an integrated information system.